Determination of Behavioural Characteristics of Different Honey bee (Apis mellifera L.) Genotypes in Eastern Anatolian Conditions - Mahir Murat Cengiz; Yaşar Erdoğan (Turkish Journal of Agriculture: Food Science and Technology)
In this study, it was investigated the stinging, robing and swarming tendencies of Buckfast, Carniolan, Caucasian and Erzurum honeybee genotypes in Eastern Anatolian conditions. In the 2015 production period, a total of 40 colonies,10 from each of Buckfast, Carniolan, Caucasian and Erzurum genotypes were used in the study. Caucasian genotype was the most gentle with 6.22±0.65 pcs/colony average number of stings, while Erzurum genotype was the most aggressive with 12.12±1.08 pcs/colony average number of stings. As a result of analysis of variance applied to average numbers of stings genotypes, the difference between the genotypes was found to be very significant in terms of tendency to stinging. In terms of tendency to robing, the Buckfast genotype ranked first with 1.57±0.17 pcs, while the Carniolan genotype had the lowest trend of robing with a value of 0.62±0.16 pcs. In terms of swarming tendency, the difference between the genotypes was statistically significant.